Stance Taking and Identity in Classroom Interactions: A Small Scale Study - Mukhlash Abrar (Master Program in Linguistics, Diponegoro University, 2020)
This present article is mainly concerned with the nature of stance-taking and identity in classroom interaction. The data of the research were taken from the interactions in an English Foreign Language class. Going through the framework of stance triangle (Du Bois, 2007), the author explored the features of stances that are frequently taken in foreign language classroom interactions and the identities enacted from the interactions. The finding of the research suggested that epistemic stance was dominantly taken in the interactions, especially by the students. This unequal distribution of stance-taking is likely to occur due to the teacher’s teaching style and students’ lack of evaluation skill. In addition, the finding indicated that both teacher and students, when they take stances, constructed diverse discourse identities, including speaker, answerer, and evaluator. These diverse identities show that the classroom interactions between teacher and students is fairly communicative and dynamic.